Bridging the Gaps Between Students’ Prior Knowledge and Skills in Writing and the Expected Thesis Outcomes: Menjembatani Kesenjangan Antara Pengetahuan dan Keterampilan Awal Mahasiswa dalam Menulis dan Hasil Tesis yang Diharapkan - Mufanti, Restu; Susilo, Andi (Universitas Muhammadiyah Sidoarjo, 2017)
This research aimed to seek the light on how the advisors made a use of feedback during supervisory panel and find out how different ways and types of feedback impacted on student-writers’ thesis outcomes. Qualitative study was applied by involving three tenured lecturers at College of Islamic Studies, in Java as the research subjects. Two data collection techniques were applied, such as interview and documentation, to trace evidence on what types of feedback used, how students noticed, and how they impacted on subsequent drafts. This study revealed that indirect feedback using error codes and commentary was the most frequent form used during the advisory session. However, the mere use of feedback could only serve a short-term impact on the development of writing, and even it seemed only to spoon-feed them which could create burdens in writing. It was quite evident that engaging them in such self-regulated and interdependence group works, through problem-solving discussion and peer review, was much worthier as compared to only ask them to process the feedback themselves.